The paradox of mental health versus mental disease in elite athletes: a scoping review - Colagrai, A. C.; Barreira, J.; Nascimento, F. T.; Fernandes, P. T. (Motriz: Revista de Educação Física, 2022)
Aim: To analyze the concepts of mental health and illness as well as the instruments used to measure them in the elite athlete. Methods: The scoping review was conducted using PubMed, SPORTDiscus, PsycINFO, and Scielo. The keywords "Mental Health" AND "Sport" AND "Athlete" were used to find studies in peer-reviewed scientific journals published in English, Spanish, and Portuguese. Studies went through four stages of analysis according to PRISMA guidelines. A total of 179 records were included in this review. Results: Recent studies suggest that health and illness should not be recognized as deviations from the norm, but as a changing construct, varying on a continuum, where, at one extreme, we have health; and, at the other, we have illness even coexisting in an orthogonal way. Between the two extremes, there are degrees of psychological well-being and distress, leading from reduced functioning to effective functioning. This indicates the need for psychological support for both the maintenance and enhancement of mental health. An alarming result was that, although most of the studies investigated mental health, they used primarily instruments focused on illness. This new perspective of health-illness brings the need for the development of new instruments that encompass protective factors and symptom screening. Conclusions: We reinforce the need for a paradigm shift in relation to the mental health of elite athletes understanding it as a changing construct that should be constantly improved and/or maintained. This change led to the need for broader assessment instruments that encompass protective factors and illness symptoms.